Design and simulation of leg exoskeleton cycling-actuated wheelchair. (28th November 2017) - Huang, Gao; Zhang, Weimin; Yu, Zhangguo; Chen, Xuechao; Meng, Fei; Ceccarelli, Marco; Huang, Qiang
This article presents a design of novel wheelchair with a leg exoskeleton for locomotion that can be powered by user legs through a cycling action. In addition, the control system is designed with leg-motion assistance for lower limb muscles to perform exercise during wheelchair motion, targeting elderly persons and users with partial hemiplegia. The simulation results characterize the dynamic operation in three possible modes, fully active, fully passive, and user passive–active action.